2005
DOI: 10.1177/070674370505000203
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Perceived Need for Mental Health Treatment, DSM Diagnosis, and Quality of Life: A Canadian Population-Based Survey

Abstract: Objectives: Prevalence estimates of mental disorders were designed to provide an indirect estimate of the need for mental health services in the community. However, recent studies have demonstrated that meeting criteria for a DSM-based disorder does not necessarily equate with need for treatment. The current investigation examined the relation between self-perceived need for mental health treatment and DSM diagnosis, with respect to quality of life (QoL) and suicidal ideation. Methods: Data came from an Ontari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
49
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 46 publications
4
49
1
1
Order By: Relevance
“…Previous studies have identified self-perceived need for treatment when respondents have either endorsed a need for mental health treatment or sought professional treatment (12,(24)(25)(26)(27). Cross-national surveys assessing perceived need for treatment have found the following results.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have identified self-perceived need for treatment when respondents have either endorsed a need for mental health treatment or sought professional treatment (12,(24)(25)(26)(27). Cross-national surveys assessing perceived need for treatment have found the following results.…”
mentioning
confidence: 99%
“…From these findings, some leaders in the field of psychiatric epidemiology have suggested that a large proportion of individuals diagnosed with mental disorders may suffer from transient or mild symptoms that do not require treatment (5,6). Conversely, community surveys have repeatedly demonstrated that a significant proportion of individuals seek or perceive a need for treatment without meeting criteria for a mental disorder (12)(13)(14)(15). These individuals could have a past mental disorder, a subthreshold mental disorder (16)(17)(18)(19)(20), or a disorder that was not assessed in the survey.…”
mentioning
confidence: 99%
See 3 more Smart Citations